(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2023)
This study aimed at identifying the role of the principals of public schools in developing the professional competencies of art education teachers in Kuwait from the point of view of the art teachers. The sample of the study consissted of (223) male and female teachers whom were selected using stratified sampling procedure. To achieave the objectives of the study, the researchers developed a questionnaire consisted of (38) paragraphs and divided into four dimensions (cognitive, performance, emotional, and orthodontic). The descriptive analytical was utillised. The study reached to the fact that the role of the principals of public schools in the development of professional competencies of art education teachers came at a medium level. In terms of the order of the dimenisions, the performaance dimension came in the first place with a high level, while the cognitive dimention came in the second rank, the emotional dimension came third, and the evaluation dimension came in the last place, all of which came with a medium level. Also, the result of the study indicated that there were no statistically significant differences at (α≤0.05) in the role of the principals of public schools in the development of professional competencies of art education teachers attributed to sex, nationality, and qualification variables, while there were statistical significant differences at (α≤0.05) in the teachers’ responses of the principals of public schools in the development of professional competencies of art education teachers attributed to the variable of experience and school stage. In the light of the results. The study recommended that the Ministry of Education should pay attention to the importance of schools principals’ role in raising the professional skills of teachers in general and art education teachers in particular, and that foundations should be placed based on the high scientific, professional, social and educational experience when selecting school principals.